PENGARUH PENDAPATAN ASLI DAERAH (PAD), DANA BAGI HASIL (DBH), DANA ALOKASI UMUM ( DAU ) DAN DANA ALOKASI KHUSUS ( DAK) TERHADAP ALOKASI BELANJA MODAL PEMERINTAH KABUPATEN/KOTA DI PROVINSI JAWA TENGAH (Jurnal Mahasiswa Pasca Sarjana, 2013)
The aim of this research was to analyze the impact of Local Original Revenue (LOR), Revenue Sharing (RS), the General Allocation Fund (GAF) and Special Allocation Fund (SAF) on the Capital Expenditure Allocation ( CEA ) of District / town Goverment in Central Java Province. This research used realization data of budget accountability of 35 district / town government in Central Java province on the periode 2007-2011 of Fiscal Year. So that the number of cases in this research were 175 data (35 cross section and 5 year time series). The research used panel data technique with Pooled Least Square ( PLS ), Fixed Effect Model ( FEM ) and Random Effect Model ( REM ).Based on model testing procedure this research used Fixed Effect Model ( FEM ). The results showed that Local Original Revenue (LOR), Revenue Sharing (RS), the General Allocation Fund (GAF) had a positive significant effect on Capital Expenditure Allocation ( CEA ) of 35 district / town government in Central Java Province while Special Allocation Fund (SAF) had no significant effect on Capital Expenditure Allocation ( CEA .  Keywords: Local Original Revenue, Revenue Sharing, General Allocation Fund, the Special Allocation Fund and Capital Expenditures.